Improving the combat capability of small police tactical groups (Law and Safety, 2024)
The article analyses the methods of enhancing the combat capability of small police tactical groups, in particular, with regard to their participation in hostilities during martial law in Ukraine. The main attention is paid to the importance of the optimal location of the commander in a small tactical group, which ensures the efficiency of performance of service and combat tasks, prompt decision-making, mobility and security of the group.The paper uses a scientific approach to improving the combat capability and tactics of small tactical groups. The following methods are used in the article: analysis, analysis of primary sources, comparative analysis, statistical and mathematical analysis, survey, expert survey, optimisation and approximation, graphical method of formations and method of optimisation of the commander’s location in a small tactical group, and method of experimental research.Different types of combat formations are studied, in particular, such as line, column, wedge, rhombus, star, snake and others, which are basic tactical elements. For each type of formation, experiments were conducted to determine the optimal location of the commander. In particular, the speed of command transmission and the risks of information loss depending on the commander’s position and the distance between the soldiers were analysed. It is established that the most optimal location of the commander is in the centre of the formation, as this ensures fast communication and minimises the risk of losses during an attack.The criterion-based approach is proposed, which includes quantitative, spatial and tactical criteria for choosing the commander’s location. The main criteria include the commander’s personal safety, efficiency of command transfer, reduction of command transformations, and minimisation of movements during re-arrangements. The empirical results confirm the importance of a comprehensive consideration of these factors to increase the combat capability of a small tactical group.The practical significance of the study lies in its possible use in the training system of the National Police of Ukraine, which will help to ensure the smooth performance of service and combat tasks and reduce personnel losses. Based on the results obtained, recommendations aimed at optimising the location of the commander in different types of combat formations have been developed.
Keywords: STG; small tactical group; effectiveness; police; combat capability; combat readiness.